Pengembangan E-Media Interaktif Nearpod dengan Model Problem Based Learning pada Hasil Belajar IPAS Kelas IV SDS Pelangi (International Forum of Researchers and Lecturers, 2025)
This study aims to develop Nearpod learning media with a valid, practical, and effective Problem-Based Learning model for the subject of Science, especially on the material of changing the form of energy for fourth grade students of Elementary School. This research is motivated by problems found through initial observations and interviews. The method used is research and development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study involved class teachers and fourth grade students of SDS Pelangi, while the object of the study focused on Nearpod learning media in Science learning on the material of changing the form of energy. Data collection techniques include interviews, tests, and questionnaires, with instruments in the form of teacher interview sheets, material validation questionnaires, media validation questionnaires, education practitioner questionnaires, and pretest and posttest questions. The results of the study showed that validation by material experts obtained an average percentage of 90% with the category